Development of a happiness measurement scale based on the Quran and Hadith using the Rasch Model - Isfara, Bunga Alodia; Usman, Irianti; Yuson, Isman Rahmani; Ramadhan, Fajar Siddiq (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2025)
Happiness has long been a central theme in psychology, both in conceptual discourse and in the development of measurement instruments. However, no existing scale integrates the moral and spiritual dimensions of happiness derived from the Qur’an and Hadith within a robust psychometric framework ensuring measurement invariance. The Qur’an and Hadith, as universal sources of guidance, encompass principles of psychological and spiritual well-being that transcend religious and cultural boundaries, consistent with the Islamic concept of rahmatan lil ‘alamin (mercy to all creation). This study aimed to develop a Qur’an- and Hadith-based happiness measurement scale using the Rasch model. The scale construction was grounded in prior qualitative research that identified three core Islamic constructs of happiness: patience (sabr), self-control (mujāhadah al-nafs), and gratitude (shukr). A total of 450 participants from diverse religious backgrounds in Indonesia completed the instrument. Data were analyzed using Confirmatory Factor Analysis (CFA) and the Rasch Model to evaluate validity, reliability, and item fit. The results indicated that the three-factor model exhibited excellent fit indices (CFI = 0.926, TLI = 0.910, RMSEA = 0.068) with high composite reliability (ω = 0.893). Rasch analysis further showed Infit MNSQ values ranging from 0.78 to 1.40 and item separation indices above 3, suggesting strong discriminant power and internal consistency. Overall, the findings demonstrate that happiness in Islam can be operationalized through measurable constructs rooted in patience, self-control, and gratitude. The proposed scale offers a psychometrically sound and universally applicable instrument grounded in Islamic ethical principles, contributing to cross-cultural research on psychological well-being. Keywords: happiness; Qur’an; hadith; Rasch model; psychometrics